ETNOBOTANI TUMBUHAN PANGAN LOKAL MASYARAKAT TAPALANG KABUPATEN MAMUJU SULAWESI BARAT - Arlinda Puspita Sari; Gaby Maulida Nurdin (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2022)
Local food plants are types of plants that are used as food by a certain community. This is related to the culture and customs of an area so it is necessary to study its ethnobotanical aspects. The aim of this study was to take an inventory of various types of local plants in Tapalang District, Mamuju Regency, West Sulawesi Province and their utilization as food ingredients. This study uses a mix method approach, which is a combination of qualitative and quantitative. The research design used is sequential exploratory. The research stages include a) interviews with respondents, b) observations of local food plants, c) sampling and identification, d) data analysis. The research results obtained include 83 species of local food plants in Tapalang District. These plant species are grouped into 41 families. Plant parts used include fruit, leaves, fruit stalks, stem starch, flowers, shoots, seeds, and tubers. These food plants are used in various forms such as direct consumption of the fruit, made into spices, made into snacks, as a mixture of dishes, cake mixes, and so on. The highest of using value species (UVs) was obtained from coconut which was used by consuming its flesh, made into oil, cooking mixtures, made into coconut milk, and as cake mixtures. The highest family using value (FUV) was obtained from the Caricaceae and Cactaceae families. Most of the local food plants in the Tapalang district can be found in the gardens and yards of residents' houses.